Restoring the balance : war powers in an age of terror - Weinberger, Seth Harold, 1970- (ABC-CLIO, 2009)
Since 9/11, one of the most dominant issues in American politics has been: what exactly is a war on terror and who is in charge of it? Previous books on this topic have fallen off the horse on either side: on the right, making military actions under the Bush administration equal to previous declared wars and ceding too much war-making power to the presidency or on the left, requiring congressional approval for any national security steps at all, contradicting much of American historical precedent. Weinberger presents a novel understanding of the Declare War clause of the Constitution (Article.